2011
DOI: 10.1007/s10773-011-0757-3
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino Oscillations in the de Sitter and the Anti-de Sitter Space-Time

Abstract: General expressions of the neutrino oscillation phase in the generally static spacetime with spherical symmetry are given. The effect of the gravitational field on the oscillation length is embodied in the gravitational red shift factor. We find that a blue shift of the oscillation length takes place when the neutrino travels out of the gravitational field. Then, we discuss the variation of the oscillation length influenced by the cosmological constant. In the de Sitter space-time, the positive cosmological co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Previously the oscillation length in the dS and AdS space-time obtained as the following respectively [36],…”
Section: Previous Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously the oscillation length in the dS and AdS space-time obtained as the following respectively [36],…”
Section: Previous Resultsmentioning
confidence: 99%
“…Recently the neutrino oscillations in the de Sitter (dS) and the anti-de Sitter (AdS) space-time has been studied [36]. It is found that in the dS space-time, the positive cosmological constant increases the oscillation length, but in the AdS space-time, the negative cosmological constant decreases the oscillation length.…”
mentioning
confidence: 99%
“…Also we used scal factor of the flat space-time, it is possible to consider non-flat metric, ds 2 = −dt 2 + a(t) 2 dr 2 1 − kr 2 + r 2 d 2 , (20) where k denotes curvature of universe. Also one can use equation of state parameter as p = (ω − 1)ρ.…”
Section: Resultsmentioning
confidence: 99%
“…It is concluded that the expansion of the universe leads to the reduction of the oscillation length. Also the neutrino physics in the de Sitter (dS) and the anti-de Sitter (AdS) space-time has been studied recently [20]. In the very recently interesting work [21] the neutrino physics in the Kerr-Newman-Kasuya (KNK) space-time considered and a comparison with the Schwarzschild, Reissner-Nordstrom (RN) performed.…”
Section: Introductionmentioning
confidence: 99%
“…If, in addition, the neutrino travels inside a gravitational field the time evolution of the quantum phase of each mass eigenstate of the superposition will also be affected differently by the gravitational interaction. One expects then a signature on the flavor oscillations due to classical gravity [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], due to the cosmic expansion of the universe [31,[33][34][35][36][37][38][39] and even due to possible quantum gravity effects [40][41][42]. Furthermore, even discussing the equivalence principle [43] and testing its possible violation is envisaged based on neutrino flavor oscillations [44,45].…”
Section: Introductionmentioning
confidence: 99%